Genes regulating levels of ω‐3 long‐chain polyunsaturated fatty acids are associated with alcohol use disorder and consumption, and broader externalizing behavior in humans. (7th August 2022) - Aliev, Fazil; Barr, Peter B.; Davies, Andrew G.; Dick, Danielle M.; Bettinger, Jill C.
Abstract: Background: Individual variation in the physiological response to alcohol is predictive of an individual's likelihood to develop alcohol use disorder (AUD). Evidence from diverse model organisms indicates that the levels of long‐chain polyunsaturated omega‐3 fatty acids (ω‐3 LC‐PUFAs) can modulate the behavioral response to ethanol and therefore may impact the propensity to develop AUD. While most ω‐3 LC‐PUFAs come from diet, humans can produce these fatty acids from shorter chain precursors through a series of enzymatic steps. Natural variation in the genes encoding these enzymes has been shown to affect ω‐3 LC‐PUFA levels. We hypothesized that variation in these genes could contribute to the susceptibility to develop AUD. Methods: We identified nine genes ( FADS1, FADS2, FADS3, ELOVL2, GCKR, ELOVL1, ACOX1, APOE, and PPARA ) that are required to generate ω‐3 LC‐PUFAs and/or have been shown or predicted to affect ω‐3 LC‐PUFA levels. Using both set‐based and gene‐based analyses we examined their association with AUD and two AUD‐related phenotypes, alcohol consumption, and an externalizing phenotype. Results: We found that the set of nine genes is associated with all three phenotypes. When examined individually, GCKR, FADS2, and ACOX1 showed significant association signals with alcohol consumption. GCKR was significantly associated with AUD. ELOVL1 and APOE were associated with externalizing. Conclusions: Taken together with observations that dietary ω‐3 LC‐PUFAs can affect ethanol‐related phenotypes, this work suggests that these fatty acids provide a link between the environmental and genetic influences on the risk of developing AUD. Abstract : Levels of omega‐3 long chain polyunsaturated fatty acids affect the physiological response to alcohol. We tested nine genes that regulate levels of these lipids for association with alcohol use disorder, alcohol consumption and externalizing phenotypes. We found that the set of genes was associated with all three phenotypes, and most of the genes in the set were associated with individual phenotypes. These findings suggest that levels of omega‐3 fatty acids may be important in the development of problematic alcohol use.